2015
DOI: 10.1039/c5cp04314j
|View full text |Cite
|
Sign up to set email alerts
|

Can we judge an oxide by its cover? The case of platinum over α-Fe2O3 from first principles

Abstract: Metal/metal-oxide interfaces appear in a wide variety of disciplines including electronics, corrosion, electrochemistry, and catalysis. Specifically, covering a metal-oxide with a metal is often thought to enhance solar energy absorption and to improve photocatalytic activity. For example, the platinum/hematite (Pt/α-Fe2O3) interface has demonstrated improved functionality. In order to advance our understanding of how metal coverage over an oxide helps performance, we characterize the geometry and electronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…For convenience, we chose to use the metal/metal/semiconductor ordering (Figure b). The lattice constant of the unit cell is an average of the lattice constants of the metal and semiconductor contacting the system, as was suggested by . The system super cell contains ten metal monolayer (FeS 2 or VS 2 ) unit cells and five semiconductor monolayer (CrS 2 , MoS 2 or CrS 2 ) unit cells, 45 atoms (Figure ).…”
Section: Methodsmentioning
confidence: 94%
“…For convenience, we chose to use the metal/metal/semiconductor ordering (Figure b). The lattice constant of the unit cell is an average of the lattice constants of the metal and semiconductor contacting the system, as was suggested by . The system super cell contains ten metal monolayer (FeS 2 or VS 2 ) unit cells and five semiconductor monolayer (CrS 2 , MoS 2 or CrS 2 ) unit cells, 45 atoms (Figure ).…”
Section: Methodsmentioning
confidence: 94%
“…The overlaps of electronic states extend the charge carrier and exhibit synergic properties . Neufeld et al study on density functional theory calculation of Pt covered Fe 2 O 3 and show that strong hybridization between Fe and Pt states reduced the electron effective mass and improve the overall charge transport …”
Section: Introductionmentioning
confidence: 99%
“…Pt(111) surface is often used as a substrate for α-Fe 2 O 3 (0001) thin film growth, because it is chemically inert, allows good epitaxy conditions and ensure conductive backcontact to improve the PEC activity in electrochemical devices. 10,21,[37][38][39][40] It is thus mandatory to determine the effect of Pt(111) substrate over hematite. In order to gather information about the chemical, structural and electronic properties in such interfaces, a molecular level investigation is required.…”
Section: Introductionmentioning
confidence: 99%
“…In order to gather information about the chemical, structural and electronic properties in such interfaces, a molecular level investigation is required. Despite numerous studies reported on α-hematite growth, mainly experimental 10,21,37,41,42 , but also some theoretical about sandwiched hematite 39,40 , the substrate-overlayer interface has not been resolved. In particular the termination (Feor O 3 ) of hematite interacted with platinum is not well-known.…”
Section: Introductionmentioning
confidence: 99%